The first case of Mpox infection in Iran during the 2022 outbreak - Maleki, Ali; Arashkia, Arash; Pouriayevali, Mohammad Hassan; Jalali, Tahmineh; Tavakoli, Mahsa; Modoodi Yaghooti, Mohammad; Ahmadi, Zahra; Niknam Oskouei, Farideh; Fereydouni, Zahra; Azadmanesh, Kayhan; Salehi‐Vaziri, Mostafa; Rohani, Mahdi (The Journal of Infection in Developing Countries, 2024)
Introduction: The unexpected outbreak of human Mpox infection beginning in some European countries that were non-endemic for Mpox stunned the world during the Coronavirus Disease 2019 (COVID-19) pandemic in May 2022. The re-emerging Mpox outbreak, which has a greater capacity for human-to-human transmission, was mainly due to traveling. In this paper, we describe the first case of the disease was observed in an Iranian woman infected by her husband who had a history of traveling to Canada. Case Report: The 34-year-old woman had flu-like syndrome with some skin rashes on her hand, finger, and arm. No antivirals were prescribed in this case, and supportive care was used to help her recover. RT-PCR and Sanger sequencing were used to analyze the sample from the oropharyngeal swab and the rash, and the results confirmed the Mpox infection. Conclusions: The risk of infectious disease outbreaks after COVID-19, such as Mpox, is of great importance, and health systems should be vigilant for timely identification and preparedness.